THE FIRST ATTEMPTS TO COLLECT THE DOCUMENTARY HERITAGE OF LITHUANIAN EXILE IN THE USA - MISIŪNAS, REMIGIJUS (Knygotyra, 2012)
Since regaining independence in 1990, the history of Lithuanian emigration has become a significant object of scientific research but the old Lithuanian emigration to the USA from the end of the 19th century up to 1948 remains analyzed very little. One of the main reasons is the lack of archival materials. The aim of this study was to analyze the first attempts to collect and preserve the heritage of the old emigration. The limited amount of periodicals, archives and author’s personal research show that the attempts to establish a heritage preservation institution failed due to the foreseen challenges of sustaining such organisation abroad. Some heritage has survived because it was gathered in personal archives and later transferred to religious institutions. A significant amount of activists saw it as an unreliable way of preservation; therefore, many of them entrusted their collections to other Lithuanian institutions during the 1918–1940 independence. Most of them were transferred to the Vytautas Magnus University in Kaunas. The Soviet occupation of Lithuania in 1940 brought new challenges to preserving the heritage. With the wave of new immigrants who arrived to the USA after 1948, the World Lithuanians’ Archive in Chicago was established, and the heritage of the old emigration was collected by collectors such as B. Kvirklys and K. Pemkus. Nevertheless, a significant amount of collections was lost after their owners’ death.